Parent-Child Communication in Understanding Learning Messages Through Online Media in the Pandemic Era - Juariyah, Juariyah; Tyanta, Yunita Putri (The Journal of Society and Media, 2021)
Communication has a big role in maintaining relationships between families, especially the relationship between parents and children, by having a good way of communication, it can have the same mindset in achieving a goal. However, the background of parents also affects the way they communicate with their children. The use of online media in learning activities, especially during the pandemic, is a choice, but it can cause various problems for poor society. The research method uses descriptive qualitative, and the data are obtained by observation and close interviews. Research subjects are poor parents and students in 4-6 grade. The technique of data sources retrival uses purposive sampling. The results of this study prove that good communication between parents and children is very much needed, especially when parents accompany children to learn through online media during a pandemic. To understand learning messages through online media, parents really have to pay attention to communication patterns with children, besides supporting factors such as the willingness of qualified learning facilities and parents who are able to understand learning messages well are children’s needs. Those things will help the child to understand the learning message. However, various factors often become obstacles, including parents’ economic background who are not able to provide maximum learning facilities and background factors which are the education of parents itself who cannot understand children's learning messages well. However, parents will do their best for their children to understand the message of online learning maximally